Characterization of a dual-CRD galectin in the silkworm Bombyx mori. (July 2016) - Rao, Xiang-Jun; Wu, Peng; Shahzad, Toufeeq; Liu, Su; Chen, Ling; Yang, Yun-Fan; Shi, Qiao; Yu, Xiao-Qiang
Abstract: Galectins (S-type lectins) are an ancient family of lectins with the β-galactoside binding activity. In mammals, galectins play essential roles in many biological processes, such as development, immune homeostasis and tumor progression. However, few studies have been devoted to their functions in insects. Here, we characterized the only dual-CRD galectin in the silkworm Bombyx mori (BmGalectin-4). BmGalectin-4 cDNA possesses an open reading frame of 1089 bp, which encodes a putative galectin of 363 amino acids containing tandem carbohydrate recognition domains (CRDs). BmGalectin-4 was expressed in various tissues but the protein was most abundant in fertilized eggs. Its transcript level in fertilized eggs was upregulated upon bacterial challenge. Recombinant BmGalectin-4 purified from Escherichia coli bound to bacterial cell wall components and bacterial cells. In addition, the recombinant protein induced bacterial agglutination, but did not have antibacterial activity against selected microorganisms. Taken together, our results suggest that BmGalectin-4 may function as a pattern recognition receptor primarily in silkworm fertilized eggs. Highlights: BmGalectin-4 is the only predicted dual-CRD galectin in the silkworm Bombyx mori . BmGalectin-4 was expressed in various examined tissues but most abundant in fertilized eggs. BmGalectin-4 transcript was induced by bacteria in fertilized eggs. Recombinant BmGalectin-4 possessed the ability to bind and agglutinate bacteria.